Comparative analyses of adeno-associated viral vector serotypes 1, 2, 5, 8 and 9 in marmoset, mouse and macaque cerebral cortex. (April 2015) - Watakabe, Akiya; Ohtsuka, Masanari; Kinoshita, Masaharu; Takaji, Masafumi; Isa, Kaoru; Mizukami, Hiroaki; Ozawa, Keiya; Isa, Tadashi; Yamamori, Tetsuo
Highlights: AAV serotypes 1, 2, 5, 8 and 9 efficiently transduced cortical cells of marmoset, mouse and macaque. AAV2 was distinct from other serotypes in neuronal tropism and small spread. Glial expression obscured neuronal transduction by CMV constructs for AAV1/5/8/9. Use of CMV promoter may lead to toxicity after long-term expression. CaMKII and Synapsin I constructs exhibited similar but slightly different cell-type preferences. Abstract: Here we investigated the transduction characteristics of adeno-associated viral vector (AAV) serotypes 1, 2, 5, 8 and 9 in the marmoset cerebral cortex. Using three constructs that each has hrGFP under ubiquitous (CMV), or neuron-specific (CaMKII and Synapsin I (SynI)) promoters, we investigated (1) the extent of viral spread, (2) cell type tropism, and (3) neuronal transduction efficiency of each serotype. AAV2 was clearly distinct from other serotypes in small spreading and neuronal tropism. We did not observe significant differences in viral spread among other serotypes. Regarding the cell tropism, AAV1, 5, 8 and 9 exhibited mostly glial expression for CMV construct. However, when the CaMKII construct was tested, cortical neurons were efficiently transduced (>∼70% in layer 3) by all serotypes, suggesting that glial expression obscured neuronal expression for CMV construct. For both SynI and CaMKII constructs, we observed generally high-level expression in large pyramidal cells especially in layer 5, as well as in parvalbumin-positive interneurons. The expression from the CaMKII construct was more uniformly observed in excitatory cells compared with SynI construct. Injection of the same viral preparations in mouse and macaque cortex resulted in essentially the same result with some species-specific differences.